Note on the diet of Ameiva edracantha (Squamata, Teiidae) in Cerros de Amotape National Park, Tumbes, Peru - Jordán, Juan C. (2011)
The diet of Ameiva edracantha Bocourt 1874, a terrestrial diurnal teiid lizard distributed in northwestern Peru and southwestern Ecuador is described for the first time. Stomach contents of fifteen individuals collected from quebrada La Angostura were analyzed. Lepidopteran larvae, coleopterans, orthopterans and spiders were the dominant preys in the lizard’s diet. Snout-vent length and head length, width and height were not correlated to prey length, width and volume. Other parameters such as profitability and prey target selection could be involved in prey selection by A. edracantha.